Przedstawic to wyrazenie w jak najprostszej postaci:
2(x+y)²-3(x-2y)(x+2y)+12xy

Oraz Oblicz wartosc przyblizona dla x=3√6 i y=-√2


Odpowiedź :

2x²+2y²-(3x+6y)(x+2y)+12xy= 2x²+2y²-4x-6xy+6xy+12xy+12xy= 2x²+2y²-4x+24xy
2(x+y)²-3(x-2y)(x+2y)+12xy = 2(x+y)(x+y) - 3(x^+2xy-2xy-4y^) + 12xy = 2(x^+ 2xy + y^) - 3x^ + 12y^ + 12xy = 2x^ + 4xy + 2y^ - 3x^ + 12y^ + 12xy = -x^ + 16xy + 14y^

x^ + 16xy + 14y^ = (3√6)^ + 16[3√6 * (-√2)] + 14*(-√2) = 54 + 16(-3√12) + -14√2 = 54 - 48√12 - 14√2 = 54 - 96√3 - 14√2